The Effect of Organic Lithium Salts on Plasma 8-Hydroxy-2' Deoxyguanosine in Bipolar Patients In Vitro; Psychopharmacology Bulletin; Vol. 50, iss. 1 - Prokopjeva V. D. Valentina Danilovna; Yarygina E. G.; Bokhan N. A. Nikolay Aleksandrovich; Plotnikov E. V. Evgeny Vladimirovich (2020, 2020)
Title screen